Assay of mitochondrial functions by resazurin in vitro - ZHANG Hai-xia; DU Guan-hua; ZHANG Jun-tian (Acta Pharmacologica Sinica, 2016)
AIM: To study the mechanism of resazurin as indicator of mitochondrial function and to develop a rapid and sensitive assay for measuring metabolic activity of isolated mitochondria from rat liver in vitro. METHODS: The screening was carried out on 96-well microtitre plates by monitoring fluorescence intensity of resazurin reduced by mitochondria. Experimental conditions were optimized and influences of several inhibitors on mitochondrial function were observed. RESULTS: Fluorescence intensity increased in a linear manner when the mitochondrial protein concentration from 5 to 50 microg protein per well was incubated with resazurin (5 micromol/L) during 230 min period at 37 degrees C. Edetic acid could promote the reduction of resazurin in mitochondria. The fluorescence intensity decreased greatly after pretreatment with NaN3, antimycin A, carbonyl cyanide p-trifluoromethoxyphenylhydrazone (FCCP), and oligomycin compared with the control. However, the typical complex I inhibitor, rotenone enhanced the fluorescence intensity without mitochondria. CONCLUSION: Using resazurin to determine mitochondrial function is sensitive, inexpensive and could be easily automated for high throughput screening.